Costa Rica - Klepeis, Alicia, 1971- (2020)
"Engaging images accompany information about Costa Rica. The combination of high-interest subject matter and narrative text is intended for students in grades 3 through 8"--
Includes bibliographical references (page 31) and index.
Ages 7-13.
Keywords: Costa Rica -- Juvenile literature